Sebaceous immunobiology - skin homeostasis, pathophysiology, coordination of innate immunity and inflammatory response and disease associations - Zouboulis, Christos C.; Coenye, Tom; He, Li; Kabashima, Kenji; Kobayashi, Tetsuro; Niemann, Catherin; Nomura, Takashi; Oláh, Attila; Picardo, Mauro; Quist, Sven R.; Sasano, Hironobu; Schneider, Marlon R.; et al. (Frontiers in Immunology, 2022)
This review presents several aspects of the innovative cncept of sebaceous immunobiology, which summarizes the numerous activities of the sebaceous gland including its classical physiological and pathophysiological tasks, namely sebum production and the development of seborrhea and acne. Sebaceous lipids, which represent 90% of the skin surface lipids in adolescents and adults, are markedly involved in the skin barrier function and perifollicular and dermal innate immune processes, leading to inflammatory skin diseases. Innovative experimental techniques using stem cell and sebocyte models have studies the roles of distinct stem cells in sebaceous gland physiology and sebocyte function control mechanisms. The sebaceous gland represents an integral part of the pilosebaceous unit and its status is connected to hair follicle morphogenesis. Interestingly, professional inflammatory cells contribute to sebocyte differentiation and homeostasis, whereas the regulation of sebaceous gland function by immune cells is antigen-independent. Inflammation is involved in the very earliest differentiation changes of the pilosebaceous unit in acne. Sebocytes behave as potent immune regulators, integrating into the innate immune responses of the skin. Expressing inflammatory mediators, sebocytes also contribute to the polarization of cutaneous T cells towards the Th17 phenotype. In addition, the immune response of the perifollicular infiltrate depends on factors produced by the sebaceous glands, mostly sebaceous lipids. Human sebocytes in vitro express functional pattern recognition receptors, which are likely to interact with bacteria in acne pathogenesis. Sex steroids, peroxisome proliferator-activated receptor ligands, neuropeptides, endocannabinoids and a selective apoptotic process contribute to a complex regulation of sebocyte-induced immunological reaction in numerous acquired and congenital skin diseases, including hair diseases and atopic dermatitis.